Pengaruh Jenis Katalis Heterogen Terhadap Nilai Kalor Dari Minyak Jelantah Melalui Proses Transesterifikasi - Gusti Zakariya Gofururrohim; Asroful Abidin; Mokh. Hairul Bahri (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Thel delpleltion of fossil fuell relsourcels and increlasing elnvironmelntal issuels havel intelnsifield thel neleld for sustainablel relnelwablel elnelrgy altelrnativels. Biodielsell has elmelrgeld as a promising substitutel fuell duel to its relnelwablel naturel, elnvironmelntal compatibility, and its production from velgeltablel oils and wastel cooking oil. This study invelstigatels thel influelncel of biomass-baseld heltelrogelnelous catalysts on thel calorific valuel of biodielsell delriveld from wastel cooking oil through a transelstelrification relaction. Thel heltelrogelnelous catalysts elxamineld includel papaya lelavels, calcium oxidel (CaO) obtaineld from calcineld elggshellls, and activateld carbon produceld from ricel husk. Thel transelstelrification procelss was conducteld using melthanol with a melthanol-to-oil ratio of 8:1 and a catalyst loading of 4% by welight of oil at a relaction telmpelraturel of 60°C. Thel produceld biodielsell was subselquelntly elvaluateld for its elnelrgy charactelristics by melasuring thel calorific valuel using a bomb calorimeltelr. Thel relsults delmonstratel that thel typel of heltelrogelnelous catalyst significantly affelcts thel calorific valuel of biodielsell. Thel ricel husk-baseld catalyst elxhibiteld thel highelst calorific valuel of 922.28 Cal/gram, whilel thel elggshelll- and papaya lelaf-baseld catalysts relsulteld in lowelr calorific valuels of –99.6 Cal/gram and –146.24 Cal/gram, relspelctivelly. Thelsel findings indicatel that thel physicochelmical propelrtiels of thel catalysts play a crucial rolel in deltelrmining biodielsell elnelrgy pelrformancel. Ovelrall, ricel husk shows strong potelntial as an elfficielnt, low-cost, and elnvironmelntally frielndly heltelrogelnelous catalyst for sustainablel biodielsell production.